2004
DOI: 10.1021/cg049914d
|View full text |Cite
|
Sign up to set email alerts
|

Size-Controllable Growth of Single Crystal In(OH)3 and In2O3 Nanocubes

Abstract: Single crystal In(OH) 3 nanocubes were synthesized by a designed novel hydrothermal treatment, and the size can be simply moderated by varying the hydrothermal temperature. By calcining the In(OH) 3 nanocubes in air at 400 °C, single crystal In 2 O 3 nanocubes were also prepared with the size slightly shrinking. Room temperature photoluminescence showed a broad photoluminescence emission spectrum in the blue-green region with its maximum intensity centered at 450 nm, which was mainly attributed to the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
111
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(117 citation statements)
references
References 21 publications
4
111
0
2
Order By: Relevance
“…5 consist of a blue-green band at 2.65 eV in the case of powder and of bands at 2.65 and 3.17 eV in the case of nanowires. The blue-green emission has also been reported in different In 2 O 3 nanostructures 17,18,20,21 while the PL band peak in the range 3.1-3.2 eV has been observed in nanowires. 7,22 The CL spectra recorded in the samples treated with the second step annealing at 650°C are similar to that shown in Fig.…”
Section: -2mentioning
confidence: 76%
See 2 more Smart Citations
“…5 consist of a blue-green band at 2.65 eV in the case of powder and of bands at 2.65 and 3.17 eV in the case of nanowires. The blue-green emission has also been reported in different In 2 O 3 nanostructures 17,18,20,21 while the PL band peak in the range 3.1-3.2 eV has been observed in nanowires. 7,22 The CL spectra recorded in the samples treated with the second step annealing at 650°C are similar to that shown in Fig.…”
Section: -2mentioning
confidence: 76%
“…Also the cubes grown in this work appear at the top of a long rod which differs from previously reported In 2 O 3 nanocubes grown by a hydrothermal method. 18 Since the starting material in the growth process is InN, compositional analysis of the arrows and other structures has been performed, by x-ray microanalysis in SEM, in order to determine the possible presence of nitrogen. Nitrogen was detected in all cases in amounts ranging from about 0.4 at.…”
Section: Growth and Luminescence Of Elongated In 2 O 3 Micro-and Nanomentioning
confidence: 99%
See 1 more Smart Citation
“…This ion has also attracted significant research attention due to its potential application as biological sensors, phosphors, electroluminescent devices, optical amplifiers or lasers when used as doping in a variety of materials 10,11 . Dutta et al 12 showed Indium hydroxides with different morphology such as spheres 13 , flowers 14,15 , cubes [16][17][18][19][20][21][22] , rods 23,24 , etc., have been synthesized by several synthesis methods. The physical and chemical properties of these powders can be influenced by particle shape and size distribution, which depend on the synthesis method.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, attention has focused on the preparation of nanomaterials with controlled sizes and morphologies [1][2][3], which are important in determining the properties of the materials. Unfortunately, real time growth mechanisms for this controlled synthesis remain unclear.…”
mentioning
confidence: 99%